Nascimento prematuro no estado do Paraná e no município de Maringá - Oliveira, Rosana Rosseto de (2015)
Premature birth is a public health issue since it is one of the main causes of child morbo-mortality. Premature births are on the increase worldwide and its etiology is complex and only slightly understood. Current thesis analyzes trends in premature births in the state of Paraná, Brazil, and in Maringá PR Brazil, coupled to factors associated with the phenomenon. Current research is part of the scientific project "Pre-term births and associated factors in the state of Paraná: prediction and prevention tools", approved by the Ethics committee. Data retrieved from the System of Information on Live Births (Sinasc) between 2000 and 2013 were used to analyze trends in prematurity in the state of Paraná and in Maringá, by polynomial regression statistical test. A case-control study, undertaken to analyze factors associated with premature birth of people resident in Maringá, comprised delivery expenses and data from interviews and clinical charts of mother and new-born children, from October 2014 to April 2015, by logistic regression analysis. In the state of Paraná, prematurity rate had a yearly increase of 0.20% (r2=0.89) (from 6.8% in 2000 to 10.5% in 2013), especially moderate prematurity increase (32 to <37 weeks) with 5.8% in 2000 to 9.0% in 2013. Prematurity rates increased in all health macroregions, with special emphasis on the northern health macroregional complex with a higher annual average increase (0.35%). Health Regional Complexes also showed a rising trend, with the exception of the 7th HRC in Pato Branco, where prematurity rates decreased (average -0.95% per year). The study of trends and factors associated to premature birth in Maringá had a 0.54% yearly mean increase (r2=0.93) with a greater participation in moderate prematurity (from 32 to <37 weeks), increasing from 7.0% in 2000 to 9.7% in 2013. The factors associated with premature birth in the 2011-2013 period comprised multiply pregnancy (OR=16.64; IC=13.24-20.92), inadequate prenatal visits (OR=2.81; IC=2.51-3.15), Apgar Index lower than 7 during the first (OR=4.07; IC=3.55-4.67) and fifth minute (OR=10.88; IC=7.71-15.36), low weight at birth (OR=38.75; IC=33.72-44.55) and congenital malformations (OR=3.18; IC=2.14-4.74). In the case of trends associated with prematurity, multiply pregnancy (0.32%; r2=0.90), caesarian section (2.38% per year) and births with congenital malformations (0.20% per year) increased. Birth with Apgar Index >7 in the fifth minute (-0.19% per year) and low weight at birth (-1.43% per year) decreased. The case-control analysis revealed that independent factors to premature births funded by the Brazilian National Health System (SUS) were hospitalization during pregnancy (ORaj=3.00; IC=1.91-4.72), mixed funding for prenatal visits (ORaj=4.11; IC=1.98-8.52), bleeding (ORaj=2.12; IC=1.31-3.45), induced delivery (ORaj=0.24; IC=0.14-0.41), previous premature birth (ORaj=2.68; IC=1.30-5.52), failure to practice physical exercises regularly during pregnancy (ORaj=3.34; IC=1.41-7.89) and less than seven prenatal visits (ORaj=1.78; IC=1.08-2.92). Independent factors associated to premature births in deliveries not funded by SUS included: hospitalization during pregnancy (ORaj=3.59; IC=2.13-6.04), multiple pregnancy (ORaj=7.52; IC=2.51-25.58), oligohydramnios (ORaj=5.70; IC=2.33-13.95) and pregnancy hypertension (ORaj=2.65; IC=1.39-5.07). Increase in premature birth in the state of Paraná requires improvement in prenatal activities with specificities for each regional unit. Increase in premature births in Maringá, especially moderate prematurity, associated with specific risk factors according to delivery funding, require efforts for the prevention of premature births, taking into consideration differences between births funded by SUS and birth funded by private health enterprises.